Spontaneous perforation of Meckel diverticulum: A case report. Issue 52 (December 2017) - Liu, Kuan-Ting; Wu, Yen-Hung
Abstract: Rationale: Meckel diverticulum (MD) is the most common congenital abnormality of the gastrointestinal tract. It is asymptomatic in the majority of patients. Perforation is a rare complication of MD and can be life-threatening. Patient concerns: A 20-year-old male patient denying previous systemic disease and complaining of epigastric pain for 5 days came to our emergency department for help. Physical examination showed right lower quadrant tenderness without muscle guarding and rebounding pain. Diagnosis: Blood examination including white blood cell, C reactive protein, liver, and renal function all showed within normal range. Abdominal computed tomography showed suspect MD in the distal ileum and enteritis at the ileum. Intervention: Perforation of MD was found while in surgery, and Meckel diverticulectomy was performed. Outcomes: The patient was discharged 7 days after the operation with stable condition. Lessons: Perforation is an uncommon complication of MD, and the symptom can mimic other acute abdominal conditions such as acute appendicitis while in the emergency space. We should take diagnosis under consideration as a differential diagnosis when we encounter patients whose impression was firstly acute appendicitis.